Design and Electromagnetic Feature Analysis of AC Rotating Machines - Masmoudi, Ahmed; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book provides the basis of the design of rotating AC machines. The first chapter puts the emphasis on the air gap magnetomotive force (MMF) of Rotating AC machines and the second chapter deals with the formulation of the rotating fields that could be generated considering different technique. The third chapter of this book focuses on the arrangement of the armature winding of fractional-slot concentrated winding permanent magnet synchronous machines, which is achieved considering the star of slots approach. Each topic is explained by case studies that show how to implement the theory into real-world design of DC machines.
Air Gap Magnetomotive Force: Formulation and Analysis -- Rotating Fields: Creation and Effects on the Machine Features -- Fractional-Slot Concentrated Windings: Design and Analysis.
Keywords: Electric power production; Electrical Power Engineering